2020
DOI: 10.18203/2320-6012.ijrms20202271
|View full text |Cite
|
Sign up to set email alerts
|

Quran recitation therapy reduces the depression levels of hemodialysis patients

Abstract: Background: Depression is one of the serious neuropsychiatric complications in CKD patients because of its high prevalence, leading to decline in the quality of life, and the potential to increase the risk of death. The psycho spiritual therapy that potential to be developed for provide support and decrease depression level is Quran recitation therapy. But studies on the effectiveness of Quran recitation therapy are still limited. The aim of this study was to reveal the effect of Quran recitation therapy on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Therefore, reciting and listening to the verses of the Holy Quran, as well as carefully and thinking about these verses can save a person from depression caused by the affairs and sufferings of life. For example, other studies showed that reciting the Quran as a nonpharmacological treatment was able to significantly reduce depression in CKD patients undergoing hemodialysis 42 and college students 43 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reciting and listening to the verses of the Holy Quran, as well as carefully and thinking about these verses can save a person from depression caused by the affairs and sufferings of life. For example, other studies showed that reciting the Quran as a nonpharmacological treatment was able to significantly reduce depression in CKD patients undergoing hemodialysis 42 and college students 43 …”
Section: Discussionmentioning
confidence: 99%
“…Reading the Quran or listening to the Quran also be a calming coping strategy because reading or listening to the Quran has an effect on many things, such as reducing anxiety in various settings (Ghiasi & Keramat, 2018;Nayef & Wahab, 2018), reducing depression levels in clinical setting (Mashitah & Lenggono, 2020), increasing sleeping quality (Hossini et al, 2019), and treatment for patients with spiritual and psychological issues (Saged et al, 2020). Previous study revealed that alpha waves activity generated from recitation of the Quran was greater than reading book, and thus it significantly affected peace of heart (Mashitah & Lenggono, 2020). Other studies have found that behavioral coping and cognitive coping were associated with calmness (Akanaeme et al, 2021;Rose & Ishak, 2019;Stanisławski, 2019).…”
Section: -83mentioning
confidence: 99%
“…Spirituality is one of the factors that influence peace of heart (Mashitah & Lenggono, 2020). Peacefulness in feelings, body, and mind is a spiritual experience that can bring peace of heart (Faletehan, 2019).…”
Section: -83mentioning
confidence: 99%
“…The incantations must not contain any polytheistic incantations in order to comply with the Islamic legal system [4]. Various studies have found the therapeutic effects of ruqyah on patients with psychological disorder such as depression [5], [6], [7] as well as some physical ailments [8], [9]. A case study in the UK has also found out that ruqyah had therapeutic effects on a patient with cluster headache, a neurological disorder [10].…”
Section: Administration and Effect Of Ruqyah Therapymentioning
confidence: 99%